TEENAGE SOCIAL LIFE IN GREEN’S LOOKING FOR ALASKA : A PSYCHOANALYTIC APPROACH - Mister Gidion Maru; Nasya Nadinia Kaya; Imelda S. Lolowang (SoCul: International Journal of Research in Social Cultural Issues, 2023)
The purpose of this study is to analyze the teenage social life in Looking for Alaska by John Green. This research is classified as a qualitative study. The primary source for data collection is the novel itself, Looking for Alaska by John Green, while secondary sources include relevant journals and articles available on the internet. These secondary sources provide additional information to support a comprehensive analysis of the research topic. The data analysis employs Freud's psychoanalytic theory, specifically focusing on the three fundamental components of Id, Ego, and Superego. The findings indicate that the teenage years encompass both positive and negative experiences during the process of growth and development. The positive things identified include group activities, collaborative learning, and read books from famous authors. Conversely, negative impacts observed involve experimentation with smoking, alcohol consumption, breaking school rules and watching porn movies. Based on this data, the writer concludes that when living life as a teenager, there are positive and negative things that are experienced during the growth process.